Legislative Process in International Organizations. Issue 3 (1st September 2020) - Conrad, Courtenay R; Monroe, Nathan W
Abstract: In this analytical essay, we advance a simple but powerful claim: scholars can better understand outcomes of international organizations (IOs) by developing theories that explicitly make assumptions about legislative process. Because process assumptions powerfully explain domestic legislative outcomes and many international assemblies demonstrate similarities to domestic legislatures, scholars could usefully employ legislative-process-centric approaches when theorizing about outcomes in world politics. Following an explication of why scholars might focus on legislative procedure, we describe several legislative procedures and highlight variance across those procedures within several well-known IOs. We also suggest that this variance and the shadow of power politics cast over IOs provides fertile ground for comparative legislative scholars—including scholars of the U.S. Congress—to develop and test new theories of legislative procedure.